Characteristics of Primary Glaucoma in Eye Outpatient Clinic of RA Basoeni Hospital, Mojokerto, Indonesia - Rayungsista, Awina (Folia Medica Indonesiana, 2018)
Glaucoma is the third cause of blindness after cataracts and refractive disorders. About 4.5 million people worldwide suffer from blindness due to primary glaucoma. A study on the characteristics of primary glaucoma in Eye Outpatient Clinic at RA Basoeni Mojokerto Hospital in the period of January-December 2016 had been performed in a descriptive cross sectional retropective study, observing: glaucoma type, gender, age, laterality, visual acuity, and intra ocular pressure (IOP). The type of primary glaucoma that most patients experienced was primary angle closure glaucoma. In primary open-angle glaucoma, the number of male patients was almost the same as female patients. Whereas, in primary angle closure glaucoma, there were more female patients than male. Primary glaucoma patients, both open and closed, were mostly >60 years old. Both primary open and angle closure glaucoma occurred mostly bilaterally. The highest visual acuity of primary glaucoma patients was mild vision loss and near-total vision loss. More glaucoma patients had IOP >21 mmHg, both in right and left eye.